Stakeholder involvement in Australian Paper and Packaging Waste Management LCA Study. - James, Karli
Intention, Goal, Scope, Background To discuss the process of stakeholder involvement as undertaken in a post consumer paper and packaging waste management LCA study conducted during 1997-2001 for the Melbourne Metropolitan Area, Victoria, Australia. Secondly, to present the findings from a survey conducted with the stakeholder groups regarding their perception of involvement in the project. Objectives To investigate the stakeholder's perception and value of being involved in the LCA study intended to generate quantitative environmental information to support debate, development and implementation of waste management practices. Methods. Stakeholders that were involved in the study, both actively and passively, were surveyed by questionnaire. Survey findings were analysed in conjunction with stakeholder interaction experiences obtained in the course of the study. Results and discussion. Respondents to the survey believed there was a sufficient level of interaction between stakeholders and researchers during the course of the project. The advisory committee approach helped to timely recognize issues and deal with them appropriately. It further assisted in the collection of life cycle inventory data and in obtaining ownership of outcomes by the research team appropriately responding to the needs and issues raised by stakeholders. Recommendations and Outlook. General recommendations for the inclusion of stakeholders in future studies are to use stakeholder interactions, wherever it is possible and practical, which in turn play an educational role, engage stakeholders from the start of the process, and allow additional time in the project plan for review stages, as well as ensuring that all relevant groups are presented-industry, industry associations, government and non-governmental organizations, and also provide sufficient material and progress for discussion at meetings.
Keywords: Australia; LCA (life cycle assessment).; Landfill; Life cycle assessment (LCA).; Paper and packaging waste management; Recycling; Stakeholder advisory committee; Stakeholder interaction